The Relationship Between the Quality of Pharmaceutical Services and Patient Safety - Rita Bambang; Herlina Jusuf; Teti Sutriyati Tuloli (GLOBAL HEALTH SCIENCE GROUP, 2026)
Pharmaceutical services are a critical component of healthcare delivery in ensuring patient safety, particularly at Community Health Centers (Puskesmas). Suboptimal pharmaceutical service quality may increase the risk of medication errors and adverse drug events, thereby compromising patient safety. However, empirical evidence regarding the contribution of pharmaceutical service quality to patient safety in primary healthcare settings remains limited. A quantitative cross-sectional study was conducted at the Sipatana Community Health Center, Gorontalo City, Indonesia, in November 2025. The study population comprised patients receiving pharmaceutical services, with 295 respondents selected through purposive sampling. Data were collected using a structured questionnaire based on national pharmaceutical service standards. The instrument demonstrated acceptable validity and reliability, with item–total correlations above the critical value and Cronbach’s alpha coefficients exceeding 0.60. Data were analyzed using the Chi-square test and stepwise logistic regression at a significance level of p < 0.05. The results showed that all dimensions of pharmaceutical service quality were significantly associated with patient safety. Management of pharmaceutical supplies and consumable medical materials, prescription review, prescription services, drug information services, prevention of medication errors, prevention of adverse drug events, and patient medication adherence were significantly associated with patient safety (p = 0.000). Monitoring of adverse drug reactions also showed a significant association (p = 0.004). Simultaneously, pharmaceutical service quality had a significant effect on patient safety (F = 23.171; p = 0.000) with an R-square value of 0.326. Stepwise regression analysis indicated that management of pharmaceutical supplies and consumable medical materials was the strongest predictor of patient safety (B = 0.284; β = 0.278). The quality of pharmaceutical services plays a significant role in ensuring patient safety at the Sipatana Community Health Center. Management of pharmaceutical supplies and consumable medical materials emerged as the primary predictor of patient safety. Strengthening pharmaceutical supply management, improving the competence of pharmaceutical personnel, and optimizing strategies for preventing medication errors and adverse drug events are essential to enhance patient safety in primary healthcare settings.